2015
DOI: 10.3892/etm.2015.2336
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MMP-9 and TIMP-3 mRNA expression in the villi of patients undergoing early spontaneous abortion: A report of 30 cases

Abstract: Abstract. The aim of the present study was to investigate the correlation of matrix metalloproteinase (MMP)-9 and tissue inhibitor of matrix metalloproteinase inhibitor (TIMP)-3 expression with spontaneous abortion (SA) during early pregnancy. The villus tissues of 30 SA cases and 20 requested abortion cases were collected during surgery and constituted the SA and normal abortion (NA) groups, respectively. The total villous RNA was extracted and the expression levels of MMP -9 and TIMP-3 mRNA were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Consistent with the findings of the current study, a case study of 30 spontaneous miscarriages and 20 requested miscarriages revealed that the mRNA expression level of MMP-9 in the spontaneous miscarriage group was higher than that in the requested miscarriage group (21).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the findings of the current study, a case study of 30 spontaneous miscarriages and 20 requested miscarriages revealed that the mRNA expression level of MMP-9 in the spontaneous miscarriage group was higher than that in the requested miscarriage group (21).…”
Section: Discussionsupporting
confidence: 91%
“…reported that the levels of MMP‐9 mRNA was significantly higher in spontaneous abortion than the corresponding levels in normal pregnant women. Moreover, they suggested that TIMP‐3 mRNA expression levels were similar in cases of spontaneous abortion and normal abortion . However, our proteomic data showed that the TIMP‐3 levels was upregulated 1.42‐fold in EPL (Supporting Information File 1).…”
Section: Discussionmentioning
confidence: 84%
“…The expression of MMPs and TIMPs during trophoblast invasion, directed by trophoblastic cells, is required. MMP-9, expressed by trophoblast cells in the embryo, and TIMP-3, expressed by maternal uterine cells, are the main enzymes involved in the invasion of trophoblast cells in the endometrium, being essential participants in the implantation process and correct development of embryos [ 296 , 297 ]. The synthesis of MMP-2 begins at the beginning of gestation, with its main function being the invasion of the trophoblastic bed [ 298 ].…”
Section: Mmps and Timps In Human Diseasesmentioning
confidence: 99%
“…A study by Anumba et al found elevated levels of TIMP-2 in women with a history of recurrent pregnancy loss (RPL), linking it to abnormal implantation and development of the placenta, as well as being a predictive marker for RPL [ 300 ]. The expression levels of MMP-9 mRNA and the MMP-9:TIMP-3 mRNA ratio are also associated with SA [ 297 ]. Dysregulated TIMP-1 expression is associated with infertility and early pregnancy loss [ 301 ].…”
Section: Mmps and Timps In Human Diseasesmentioning
confidence: 99%